2022
DOI: 10.1007/s00170-022-09503-7
|View full text |Cite
|
Sign up to set email alerts
|

Residual oxygen content and powder recycling: effects on microstructure and mechanical properties of additively manufactured Ti-6Al-4V parts

Abstract: The laser-based powder bed fusion of metals (PBF-LB/M) offers a variety of advantages over conventional processing techniques and the possibility to recycle and reuse powder increases its sustainability. However, the process and resulting part properties are influenced by a variety of factors including powder recycling grade and residual oxygen content of the process atmosphere. Especially in terms of reactive materials like Ti-6Al-4V, oxidation during processing and recycling determines process stability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Larger agglomerates (satellite particles) removed during sieving might be the main reason for the narrowing of the PSD, and, together with the reduction of the humidity of the powder, also results in improved flowability and consequently the lower porosity 18 . It is assumed that reusing the powder would have an influence on its porosity 22 . The conclusions of previous studies are, however, contradictory in this regard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger agglomerates (satellite particles) removed during sieving might be the main reason for the narrowing of the PSD, and, together with the reduction of the humidity of the powder, also results in improved flowability and consequently the lower porosity 18 . It is assumed that reusing the powder would have an influence on its porosity 22 . The conclusions of previous studies are, however, contradictory in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of recycling also has a large impact on the properties of a 3D printed object. Some influences of exposing the powder to heat and gases in the printing atmosphere, such as oxygen uptake, and changes to the chemical composition and microstructure, cannot be restrained by recycling 15 , 22 , 28 , 29 . In order to achieve the target properties, it is therefore of great interest to understand the impacts of these factors on the properties of the final object.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the microstructure of the powders, it is found that both the virgin and reused Ti6Al4V powders consist of a dark brown with an irregular lighter region after etching with ammonium bifluoride (figures 13(b-i) and (b-ii)) [247]. However, the lamellar structure can be observed in the lighter area for reused powders (figure 13(b-ii)) Yet, the mechanisms behind the variation in the microstructure or phase composition were not given in the study.…”
Section: Powder Reusability Of Titanium and Titanium Alloymentioning
confidence: 99%
“…Finally, it is reported that the density of the samples fabricated using virgin and reused CP-Ti powders for 10 times [209] is the same. However, Soltani-Tehrani et al [183] observed that the porosity of the parts tended to decrease first and then increase as the [247], with permission from Springer Nature. (c) EBSD map and phase distribution of virgin (i and ii) and reused (iii and iv) samples.…”
Section: Powder Reusability Of Titanium and Titanium Alloymentioning
confidence: 99%
See 1 more Smart Citation